2003
DOI: 10.1177/0891243203257477
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking, Migration, and the Law

Abstract: The Trafficking Victims’ Protection Act of 2000 has been presented as an important tool in combatingthe exploitation and abuse of undocumented workers, especially those forced into prostitution. Through a close reading of the legislation and the debates surrounding its passage, this article argues that the law makes strategic use of anxieties over sexuality, gender, and immigration to further curtail migration. The law does so through the use of misleading statistics creating a moral panic around “sexual slave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(41 citation statements)
references
References 1 publication
(1 reference statement)
0
37
0
1
Order By: Relevance
“…In terms of solutions, these alternative voices propose legalizing prostitution, treating prostitutes as workers rather than victims, and helping them obtain safer working conditions and health care. They also call for more liberalized immigration laws in the USA and Western Europe (Andrijasevic 2007;Chapkis 2003;Kempadoo 2005;Kinney 2006). …”
Section: Us Anti-trafficking Policymentioning
confidence: 97%
See 2 more Smart Citations
“…In terms of solutions, these alternative voices propose legalizing prostitution, treating prostitutes as workers rather than victims, and helping them obtain safer working conditions and health care. They also call for more liberalized immigration laws in the USA and Western Europe (Andrijasevic 2007;Chapkis 2003;Kempadoo 2005;Kinney 2006). …”
Section: Us Anti-trafficking Policymentioning
confidence: 97%
“…Another group of scholars and activists criticize US policy from a "sex-positive" feminist (e.g., see Agustin 2007;Andrijasevic 2007;Chapkis 2003;Doezema 2000;Kinney 2006;Kuo 2002) or post-colonialism perspective (e.g., see Kempadoo 2005;Outshoorn 2005). These views are echoed frequently in the leading progressive news magazines (e.g., see Cockburn 2006;Critchell 2003;Jones 2007;Katayama 2005;Lustig 2007;Nathan 2005;Schafer 2005).…”
Section: Us Anti-trafficking Policymentioning
confidence: 98%
See 1 more Smart Citation
“…The studies have also shown that such an understanding of trafficking fails to address the convergence between anti-trafficking and anti-immigration policies. Moreover, the international instruments set in place to counter trafficking (such as the Palermo Protocol) have been criticized for actually facilitating the cooperation between states to prevent irregular migration, rather than protecting or giving restitution to the victims of crime or migrants in situations of labour exploitation (Chapkis, 2003: Gallagher, 2001). …”
Section: Sites Of Productionmentioning
confidence: 99%
“…Per-Anders Edin, et al (2004) evaluates the rules stipulated in the immigration policy particularly in Sweden and shows that immigrants are likely to experience substantial long-term losses. Chapkis (2003) argues that the Trafficking Victims Protection Act of 2000 in the United States is meant to combat exploitation and abuse of undocumented immigrant workers. However some misleading statistics have created a moral panic around an anti-immigrant policy that fails to help victims of sexual slavery and guilty immigrants.…”
Section: Introductionmentioning
confidence: 99%